To the question of the thermal conductivity of metallic nanothreads and nanofilms - Yurov, V.M.; Ranova, G.A.; Guchenko, S.A.; Laurinas, V.Ch. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
In recent years, attention has been growing in the study of the thermophysical properties of nanostructures, which is due to the opportunities that open with the use of these structures in virtually all fields of science, technology, medicine, etc. Studies show that there are significant differences in the nature of heat transfer within macroscopic bodies and in nanostructures. Another feature of this problem is the large variety of objects that require the development of special theoretical and experimental research methods. In this connection, the issues of heat transfer in solid-state nanostructures are currently an area of active research. As shown by us in a number of papers, the equations (1)–(3) obtained have a universal character and are valid for the dimensional dependence of many properties of nanostructures, including thermophysical ones. In the present paper, this approach is used in considering the thermal conductivity and electrical conductivity of metallic nanostructures and some typical problems of thermal conductivity of thin films. It follows from the results presented in the paper that for metal nanostructures the Fuchs-Sondheimer model works well when taking into account the dimensional dependence of the mean free path of an electron. In all the guidelines for calculating the thermal fields of thin coatings of space and aviation equipment, we start with the classical heat conduction equations, where the thermal conductivity coefficient is assumed to be a constant value. In this paper, we showed that when the thickness of a metal film is less than 50–100 nm, its physical properties are affected by dimensional effects. The problem of the thermal field of an unlimited plate of small thickness is considered. It is shown that the heat field of a nanoplate depends both on the material of the plate through the coefficient of thermal conductivity of a massive sample, and on the size factor. In the classical case, there is no such dependence.
Металл наножіптердің жəне наноқабыршақтардың жылуөткізгіштігінің мəселесіне
К вопросу о теплопроводности металлических нанонитей и нанопленок
Keywords: thermal conductivity; electrical conductivity; nanowire; nanofilms; size effect; thermal physics